The Father's Girls $1! =(BWho they are and what they ought to knows - Tewe, Titiola (Phoster Solutions, 2007)
The Father's Girls' presents the transforming love of the Father and addresses the misconceptions of popular culture to help today's young women to live complete, focused and creative lives.
Keywords: Girls'; Non-Fiction; Women